Technology Adoption Under Relative Factor Price Uncertainty: The Putty-Clay Investment Model - Hiroyuki Kasahara (Queen's University, Department of Economics, 2003)
A plant has more flexibility in choosing among different technologies before undertaking an investment than after installing a specific machine. This paper argues that the irreversibility of factor intensity choice may play an important role in explaining the dynamics of investment in the presence of relative factor price uncertainty. A higher degree of irreversibility in the choice of factor intensity—characterized by the ex ante elasticity of substitution—leads to a larger negative effect of uncertainty in relative factor prices on investment. The empirical implications are examined using the plant-level Chilean manufacturing data for the period of time-varying exchange rate volatility. The econometric results show that the elasticity of substitution between imported materials and domestic materials is substantially higher at the time of a large investment and suggest that the irreversibility of factor intensity choice may play an important role in explaining the impact of exchange rate volatility on investment.
Keywords: D81; E22; O33; 330; Irreversible Investment; Putty-Clay; Technology Adoption; Uncertainty